A co-sol-emulsion-gel synthesis of tunable and uniform hollow carbon nanospheres with interconnected mesoporous shells. Issue 1 (2nd December 2015) - Hou, Jianhua; Cao, Tai; Idrees, Faryal; Cao, Chuanbao
Abstract : Monodispersed tunable nanoscale hollow carbon spheres with an open interconnected mesoporous shell have been synthesized by a co-sol-emulsion-gel method. Abstract : Monodispersed mesoporous hollow spheres of polymer–silica and carbon–silica nanocomposites with an "interpenetration twin" nanostructure have been successfully synthesized by a co-sol-emulsion-gel method. The obtained mesoporous hollow carbon spheres (MHCSs) exhibited an open interconnected mesoporous shell that is endowed with high specific surface area ( S BET, 2106–2225 m 2 g −1 ) and large pore volume (1.95–2.53 cm 3 g −1 ). Interestingly, the diameter of the uniform MHCSs could be precisely tuned on demand, as an effective electrode material in supercapacitors, MHCSs with a diameter of 90 nm deliver the shortest time constant ( τ 0 = 0.75 s), which is highly beneficial for rate capacitance (180 F g −1 at 100 A g −1, a full charge–discharge within 0.9 s) and cyclic retainability (3% loss after 20 000 cycles). The newly developed synthesis route leads to unique interconnected mesoporous hollow carbonaceous spheres with open-framework structures, providing a new material platform in energy storage.